DEVELOPING THE COGNITIVE COMPETENCE OF SOCIAL SECTOR EMPLOYEES BASED ON DIGITAL TECHNOLOGIES AS A PEDAGOGICAL PROBLEM (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the development of the cognitive competence of social sector employees through digital technologies as a pedagogical problem. In the modern digital environment, social sector professionals are required to possess advanced analytical thinking, information processing, problem-solving, and decision-making skills. In this regard, digital technologies are considered an effective tool for forming and enhancing cognitive competence. The study highlights the pedagogical potential of digital learning platforms, artificial intelligence, online training, and interactive technologies, analyzing their impact on the professional development of social sector workers. The findings demonstrate the necessity of a systematic and integrated approach to this process.